JS07.4.A Correspondence of glutamine and glycine imaging based on 7T MRSI to amino acid PET. (5th September 2022) - Hangel, G; Rausch, I; Furtner, J; Roetzer-Pejrimovsky, T; Preusser, M; Bogner, W; Rössler, K; Trattnig, S; Traub-Weidinger, T; Widhalm, G
Abstract: Background: New approaches for 7 Tesla magnetic resonance spectroscopic imaging (MRSI) allow the simultaneous imaging of multiple neuro-oncological biomarkers with 3-4 mm resolution in clinically feasible measurement times. Specifically, the amino acids glutamine (Gln) and Glycine (Gly), were previously limited to single voxel detection at lower fields. Both could add to our capabilities to resolve heterogeneous tumour metabolism. Purpose: To progress the validation of Gln and Gly as neuro-oncological markers by conducting the first comparison to amino acid PET in a cohort of glioma patients. Material and Methods: In 24 glioma patients (WHO 2021 classification), we quantitatively compared 7T MRSI (3D, 3.4 mm isotropic resolution, 15 min scan time) and routine PET (FET or MET). Within manual tumour segmentations, we defined hotspot volumes of interest (VOI) for the ratios of total choline (tCho, clinical standard reference), Gln, Gly to total N-acetylaspartate (tNAA) and PET tumour-to-brain ratios (TBR), all with a cut-off threshold of 1.6. For these VOIs, we calculated VOI volumes and median ratios as well as Dice similarity coefficients (DSC) and centre of intensity distance (CoI), between MRSI and PET ratios. Results: We found that Gln and Gly ratios to tNAA had a higher correspondence to PET-based amino acid metabolism than tCho. Our resulting median VOI volumes were 19.08±23.10 cm³ for tCho/tNAA, 33.68±24.60 cm³ for Gln/tNAA, and 22.38±18.49 cm³ for Gly/tNAA compared to 24.33±30.46 cm³ for PET, with correlation coefficients >0.5 for all MRSI hotspot values in relation to PET volumes. Median ratios were 0.52±0.13 for tCho/tNAA, 0.61±0.25 for Gln/tNAA, 0.33±0.15 for Gly/tNAA and 2.11±0.42 for PET. The median DSCs to PET amounted to 0.53±0.36 for tCho/tNAA, 0.66±0.40 for Gln/tNAA, and 0.57±0.36 for Gly/tNAA, while the median CoI distances were 0.56±0.43 cm for tCho/tNAA, 0.39±0.22 cm for Gln/tNAA, and 0.45±0.48 cm for Gly/tNAA. Conclusion: With this first study that compared high-resolution 3D-MRSI at 7 Tesla to amino acid PET and a quantitative evaluation, we demonstrated that Gln and Gly corresponded better to PET than tCho, which is the main marker used in clinical MR, both within the study and compared to previous literature. Future research is needed to clearly define the benefits of 7T MRSI for neuro-oncology such as the identification of tumour microenvironments or non-invasive determination of molecular-pathologic markers. Gln could be further explored by the application of Gln-based PET tracers to MR-PET. We still see further developments of MRSI methods, such as motion correction or absolute quantification of concentrations instead of ratios, as necessary to obtain such goals.